Correlation Between Lactate Dehydrogenase (LDH) Values and Aspects Score at the Beginning of Treatment in Acute Ischemic Stroke - Lathifatul Fikriyah; M. Saiful Ardhi; Sita Setyowatie (Eduvest - Journal of Universal Studies, 2025)
On a global scale, stroke ranks as the second biggest killer and the third most prevalent cause of disability. Metabolic acidosis occurs when oxygen is not present in the blood after an ischemic stroke. The purpose of this research was to show that acute ischemic stroke patients treated at Surabaya's Dr. Soetomo General Hospital had an association between their lactate dehydrogenase (LDH) serum level and their ASPECTS score before treatment began. Sampling was conducted using consecutive admissions methods. The ASPECTS score and LDH serum examination were assessed and taken upon admission. Thirty individuals were enrolled in the trial; sixteen (53.3%) were male and fourteen (46.7%) were female. The results demonstrate a relationship or correlation between LDH and ASPECT Score according to the Spearman test. The p-value is 0.003, which is less than 0.05, indicating a meaningful relationship or correlation between LDH and ASPECTS Score based on statistical tests. The r-value of -0.279 indicates a weak inverse relationship (27.9% strength) between the ASPECT score variable and LDH, according to the results of the correlation test. The relationship between LDH and ASPECT Score is negative, where if the ASPECT score value is high, the LDH value will be low, and vice versa. In conclusion, this study demonstrates a statistically significant (p = 0.003) but weak inverse correlation (r = -0.279) between serum LDH levels and ASPECT scores in acute ischemic stroke patients.